2, 4-Dinitrotoluene removal in aerobic granular biomass sequencing batch reactors. (April 2017) - Kiran Kumar Reddy, G.; Sarvajith, M.; Nancharaiah, Y.V.; Venugopalan, V.P.
Abstract: Aerobic granules were cultivated in sequencing batch reactor (SBR) by feeding 2, 4-dinitrotoluene (2, 4-DNT) along with acetate. Aerobic granules with an SVI10 of 34.57 ± 2.6 mL g −1 and average diameter of 0.78 ± 0.3 mm were formed during 30 d of SBR start-up period. In an alternative approach, aerobic granules cultivated using acetate as carbon source were acclimatized and evaluated for 2, 4-DNT removal. In both the approaches, the aerobic granules exhibited rapid 2, 4-DNT removal wherein >90% of 10 mg L −1 2, 4-DNT was removed within 24 h cycle period. The aerobic granules also exhibited ammonium-nitrogen and phosphorus removal in addition to organic carbon removal, indicating that presence of 2, 4-DNT did not negatively affect nutrient removal. In aerobic granular biomass reactors, most of the organic carbon was consumed within the first 6 h while, majority of the 2, 4-DNT was removed during the 24 h cycle period. HPLC analysis detected smaller amounts of 2-amino-4-nitrotoluene, a biotransformation product of 2, 4-DNT. 2, 4-DNT removal by granules under anaerobic conditions was observed to be much smaller compared to the aerobic SBR. Thus, 2, 4-DNT removal by aerobic granules was likely mediated by combination of both oxidative and reductive pathways. Although, the mechanisms of 2, 4-DNT removal requires further investigations, effective and stable removal of 2, 4-DNT in aerobic granular biomass reactors offers practical possibilities for treatment of wastewaters from ammunition factories. Highlights: Aerobic granules cultivated by feeding acetate plus 2, 4-dinitrotoluene for the first time. 2, 4-dinitrotoluene was rapidly removed when fed along with acetate or lactate. 2-amino-4-nitrotoluene was formed in minor amounts during 2, 4-DNT removal. Aerobic granules removed 2, 4-DNT by both oxidative and reductive pathways. Nutrient removal by aerobic granules was not impacted by 10 mg L −1 2, 4-DNT.